PERBANDINGAN EFESIENSI DAN EFEKTIVITAS PENGENDALIAN HAMA TIKUS (RATTUS TIOMANICUS) DENGAN CARA KIMIAWI DAN BIOLOGI DI PT. TRITUNGGAL SENTRA BUANA - Muhammad Ihza Mahendra; Jamaluddin; Jumri (Politeknik Pertanian Negeri Samarinda, 2022)
This study aims to determine the effectiveness of cleric rodenticide, the active ingredient brodifakum 0.05% and the effectiveness of using Tyto alba which is used as a natural enemy/predator of rats. In addition, to find out the costs incurred for controlling the use of cleric poison and the costs incurred for tyto alba in oil palm.This research was conducted at PT. Tritunggal Sentra Buana Saliki Village, Kec. Muara Badak was held for 3 months from September to December 2020.The method used in this study is a strengthened field observation method and secondary data, including company documents and libraries, as well as in-depth discussions with related R&D assistants in the field. The results are then analyzed and evaluated descriptively.Based on the results of this study, controlling rat pests using owls and cleric poison can effectively reduce severe rat attacks to light attacks. Economically, using owl predators can save on the cost of controlling rats, when compared to cleric poison, the costs incurred are certainly much higher because of the cost of poison and the cost of kindergarten wages.